2015
DOI: 10.1007/s10661-015-4269-0
|View full text |Cite
|
Sign up to set email alerts
|

Levels of organochlorine pesticides in the blood of people living in areas of intensive pesticide use in Sudan

Abstract: Ninety-six human blood samples were collected from six locations that represent areas of intensive pesticide use in Sudan, which included irrigated cotton schemes (Wad Medani, Hasaheesa, Elmanagil, and Elfaw) and sugarcane schemes (Kenana and Gunaid). Blood samples were analyzed for organochlorine pesticide residues by gas liquid chromatography (GLC) equipped with an electron capture detector (ECD). Residues of p,p'-dichlorodiphenyldichloroethylene (DDE), heptachlor epoxide, γ-HCH, and dieldrin were detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…From different studies, endosulfan is an endocrine disruptor, mimicking estrogen at very low concentration and may lead to risk of breast cancer, a neurotoxin, parkinson’s disease and birth defects [29] , [30] . In the present study, Aldrin was not detected in all blood samples analyzed, similar study in Sudan reported the same result [31] . This may be due to their ready conversion to its metabolite dieldrin.…”
Section: Resultssupporting
confidence: 85%
“…From different studies, endosulfan is an endocrine disruptor, mimicking estrogen at very low concentration and may lead to risk of breast cancer, a neurotoxin, parkinson’s disease and birth defects [29] , [30] . In the present study, Aldrin was not detected in all blood samples analyzed, similar study in Sudan reported the same result [31] . This may be due to their ready conversion to its metabolite dieldrin.…”
Section: Resultssupporting
confidence: 85%
“…Various blood levels of OCPs were documented in populations from several countries141516. In India, reported serum levels were as high as 743 ng/mL for DDT and 627 ng/mL for HCH16.…”
mentioning
confidence: 99%
“…Therefore, the presence of its residues and/or its metabolite endosulfan sulfate is expected. 28 29 The absence of p,p-DDT residues may be explained by the possible environmental conversions to p,p-DDE and p,p-DDD as found in previous studies. 26 , 30 – 33…”
Section: Discussionmentioning
confidence: 58%